2016
DOI: 10.1055/s-0042-111197
|View full text |Cite
|
Sign up to set email alerts
|

Trinkverhalten von Personen verschiedener Herkunftsregionen in Deutschland: Ein Vergleich mit Personen ohne Migrationshintergrund

Abstract: Zusammenfassung Ziel: Es wurden Personen mit Migrationshintergrund aus verschiedenen Herkunftsregionen hinsichtlich ihres Alkoholkonsums mit Personen ohne Migrationshintergrund verglichen. Methodik: Daten des Epidemiologischen Suchtsurveys (ESA) 2012 wurden ausgewertet (n=9 084). Personen mit Migrationshintergrund wurden ihrer Herkunft entsprechend in 10 Gruppen aufgeteilt. Als Indikatoren zur Erfassung des Alkoholkonsums dienten Abstinenz, Durchschnittskonsum und episodisches Rauschtrinken. Inferenzstatistisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Among women, long weekly working hours are positively associated with alcohol consumption [46]. With regard to migration background, people from Turkey, which represents the most common foreign country of origin in Germany, have significantly higher abstinence rates than people with no migration background [46, 48]. Thus, our study suggests that correlates of alcohol consumption do not differ substantially between parents and nonparents in the general population, with one notable exception.…”
Section: Discussionmentioning
confidence: 83%
“…Among women, long weekly working hours are positively associated with alcohol consumption [46]. With regard to migration background, people from Turkey, which represents the most common foreign country of origin in Germany, have significantly higher abstinence rates than people with no migration background [46, 48]. Thus, our study suggests that correlates of alcohol consumption do not differ substantially between parents and nonparents in the general population, with one notable exception.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, in the present study people with a German citizenship were more likely to be in the drinking lifestyle class. A study by Strupf and colleagues39 also reported differences among people with and without migration background considering alcohol consumption, but further research is needed to assess motives for EHD among various cultural groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests associations between alcohol consumption and the presence of a migration background for e.g. cultural or religious reasons depending on the country of birth [ 14 , 34 , 35 ]. Due to the small number of cases and the lack of relevant determinants in the KiGGS survey (such as religious affiliation), this association cannot be further investigated in this article.…”
Section: Discussionmentioning
confidence: 99%